Gratitude as a Determinant of Psychological Well-Being in Adolescents: an Islamic Psychology Perspective - Reza, Iredho Fani; Kamilah, Salsabila Nur; Latifa, Rena; Lisfarika Napitupulu (Psikis : Jurnal Psikologi Islami, 2024)
The psychological well-being of teenagers is still relatively low because teenagers are entering a period of searching for their identity, so teenagers are very vulnerable to their psychological well-being. This research aimed to find out the influence of gratitude on psychological well-being in adolescents. This research used a quantitative type of research with a survey approach. The total research respondents were 358 taken by using the Convenience Sampling Technique with the characteristics: 1) Adolescents aged 16-20 years; 2) Domicile in Palembang; 3) Willing to be a research respondent. The measuring instruments were Ryff's Psychological Well-Being Scale (RPWB) (1989), and The Gratitude Questionnaire Six Item Form (GQ-6) (2002). The research data collection method used an online survey with Google Form platform. The data analysis method used Pearson's Correlations Technique with JASP (Jeffrey's Amazing Statistics Program) version 0.18. The study concluded that there was a significant influence of gratitude on psychological well-being in adolescents (p = <0.001). The higher the level of gratitude in teenagers, the higher the psychological well-being of teenagers. The contribution of gratitude to psychological well-being was 21.1%.